The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jwmg.21503
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of neonate eastern box turtles with prescribed fire implications

Abstract: Little is known about the movements and behavior of neonate eastern box turtles (Terrapene carolina carolina). We investigated spatial ecology of neonate eastern box turtles at 4 upland openings in the Manistee National Forest, Michigan, USA, 2012–2016. We protected nests and used radio‐telemetry to document dispersal from nests, land cover types used for overwintering, and residency time of neonates in natal openings. We used binomial logistic regression to model probabilities of overwintering in natal openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Limited direct dispersal data (e.g., from mark-recapture or radio-telemetry studies) exist for Eastern Box Turtles. Laarman et al (2018) show that neonate dispersal from nests at our study site is extremely limited within the first activity season. Mean straight-line dispersal distance from nests to the first overwintering sites was less than 20.0 m (Laarman et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Limited direct dispersal data (e.g., from mark-recapture or radio-telemetry studies) exist for Eastern Box Turtles. Laarman et al (2018) show that neonate dispersal from nests at our study site is extremely limited within the first activity season. Mean straight-line dispersal distance from nests to the first overwintering sites was less than 20.0 m (Laarman et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Laarman et al (2018) show that neonate dispersal from nests at our study site is extremely limited within the first activity season. Mean straight-line dispersal distance from nests to the first overwintering sites was less than 20.0 m (Laarman et al, 2018). Although movement away from the nest tended to increase in the second activity season, Laarman et al (2018) were unable to examine movement differences by sex as sexing these age classes is impossible without using invasive methods.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Nesting relatively close to edges, despite lower nest success near edges, is suggestive of a trade-off between selection pressure on a different life stage: perhaps hatchlings' access to other macrohabitat types that may confer higher juvenile survival is an important driver of nesting relatively close to edges. We found no evidence of increased juvenile survival from nests near macrohabitat edges, but nest distance to forest edge was the strongest predictor of a juvenile's eventual overwintering site in a more northern box turtle population (Laarman et al, 2018), and in a separate study on these same populations we found that most hatchling box turtles overwintered in forest or forest edge habitat (Hulbert, 2020). A useful avenue for future research would be to explore other potential life-history tradeoffs that might explain the propensity to nest near edges that confer relatively low nest success or determine if this is simply a negative edge effect, and to identify the mechanism that might underlie such an edge effect.…”
Section: Discussionmentioning
confidence: 67%